Analisis Isi Pesan Akidah pada Whatsapp Group Hijrah Fisabilillah - Dhea Riza Armyfa; Parihat Kamil; Sausan Muhammad Sholeh (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. In this era the social media is widely used as a tool of Islamic preaching (dakwah), namely WhatsApp Groups as one of the platforms for religious communication. The group of Hijrah Fisabilillah is a digital community where actively disseminates the messages in relation to Islamic creed (akidah). This study aims to analyze the content of akidah messages in the group which is based on Bernard Berelson’s theory, this study includes the message categories, patterns of message delivery, and the message tendencies. This research uses a qualitative method with a content analysis approach. The data were collected through documentation during the month of Ramadan 1446 H/2025 CE. The results show that the akidah messages in this group comprehensively reflect the teachings of tauhid, including rububiyah, uluhiyah, and asma’ wa sifat in the WhatsApp Group. The delivery patterns are concerning such as narrative, persuasive, and educational, while the message tendencies emphasize the introspective calls and the strengthening of tauhid. In conclusion, the WhatsApp Group of Hijrah Fisabilillah serves as an effective medium for dakwah, positively and interactively shaping the members’ understanding of akidah. Abstrak. Di era ini , media sosial banyak digunakan sebagai sarana dakwah Islam, salah satunya adalah Grup WhatsApp sebagai platform komunikasi keagamaan. Grup Hijrah Fisabilillah merupakan komunitas digital yang aktif menyebarkan pesan-pesan yang berkaitan dengan akidah Islam. Penelitian ini bertujuan untuk menganalisis isi pesan akidah dalam grup tersebut berdasarkan teori Bernard Berelson, yang mencakup kategori pesan, pola penyampaian pesan, dan kecenderungan isi pesan. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis isi. Data dikumpulkan melalui dokumentasi selama bulan Ramadhan 1446 H/2025 M. Hasil penelitian menunjukkan bahwa pesan-pesan akidah dalam grup ini secara menyeluruh mencerminkan ajaran tauhid, yang meliputi tauhid rububiyah, uluhiyah, dan asma’ wa sifat. Pola penyampaian pesan yang digunakan meliputi naratif, persuasif, dan edukatif, dengan kecenderungan pesan yang menekankan ajakan untuk introspeksi dan penguatan tauhid. Kesimpulannya, Grup WhatsApp Hijrah Fisabilillah menjadi media dakwah yang efektif dalam membentuk pemahaman akidah anggota secara positif dan interaktif.